CLDN18.1 attenuates malignancy and related signaling pathways of lung adenocarcinoma in vivo and in vitro. Issue 12 (16th October 2018) - Luo, Jiao; Chimge, Nyam‐Osor; Zhou, Beiyun; Flodby, Per; Castaldi, Alessandra; Firth, Amy L.; Liu, Yixin; Wang, Hongjun; Yang, Chenchen; Marconett, Crystal N.; Crandall, Edward D.; Offringa, Ite A.; et al.
Abstract : Claudins are a family of transmembrane proteins integral to the structure and function of tight junctions (TJ). Disruption of TJ and alterations in claudin expression are important features of invasive and metastatic cancer cells. Expression of CLDN18.1, the lung‐specific isoform of CLDN18, is markedly decreased in lung adenocarcinoma (LuAd). Furthermore, we recently observed that aged Cldn18 −/− mice have increased propensity to develop LuAd. We now demonstrate that CLDN18.1 expression correlates inversely with promoter methylation and with LuAd patient mortality. In addition, when restored in LuAd cells that have lost expression, CLDN18.1 markedly attenuates malignant properties including xenograft tumor growth in vivo as well as cell proliferation, migration, invasion and anchorage‐independent colony formation in vitro . Based on high throughput analyses of Cldn18 −/− murine lung alveolar epithelial type II cells, as well as CLDN18.1‐repleted human LuAd cells, we hypothesized and subsequently confirmed by Western analysis that CLDN18.1 inhibits insulin‐like growth factor‐1 receptor (IGF‐1R) and AKT phosphorylation. Consistent with recent data in Cldn18 −/− knockout mice, expression of CLDN18.1 in human LuAd cells also decreased expression of transcriptional co‐activator with PDZ‐binding motif (TAZ) and Yes‐associated protein (YAP) and their target genes, contributing to its tumor suppressor activity. Moreover, analysis of LuAd cells in which YAP and/or TAZ are silenced with siRNA suggests that inhibition of TAZ, and possibly YAP, is also involved in CLDN18.1‐mediated AKT inactivation. Taken together, these data indicate a tumor suppressor role for CLDN18.1 in LuAd mediated by a regulatory network that encompasses YAP/TAZ, IGF‐1R and AKT signaling. Abstract : What's new? Mice deficient in expression of the lung‐specific claudin, CLDN18.1, develop lung cancer but insight into the precise role of this tight junction protein in lung cancer suppression remains limited. Here the authors show that CLDN18.1 expression in human lung adenocarcinomas is inversely correlated with promoter methylation and patient mortality. Restoration of CLDN18.1 expression in human lung cancer cells suppresses cell proliferation and impairs the protein kinase B/AKT signaling pathway, implicating CLDN18.1 as a new prognostic marker and therapeutic target in lung adenocarcinoma patients.